2006
DOI: 10.1073/pnas.0606239103
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of protein structural classes and protein sequence families

Abstract: In protein structure space, protein structures cluster into four elongated regions when mapped based solely on similarity among the 3D structures. These four regions correspond to the four major classes of present-day proteins defined by the contents of secondary structure types and their topological arrangement. Evolution of and restriction to these four classes suggest that, in most cases, the evolution of genes may have been constrained or selected to those genetic changes that results in structurally stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 27 publications
(26 reference statements)
2
81
0
1
Order By: Relevance
“…Previous work showed that the alpha/beta domains are older (19), more stable (36), more frequently involved in domain fusion events (32), and are associated with high functional diversity (20). Our analysis shows two additional unique features of these domains: they lie in a tightly connected region of protein space and their motifs mix-and-join with a wider range of motifs.…”
Section: The Motif Network Reveals the Ubiquitous Reuse Of Motifs Inmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous work showed that the alpha/beta domains are older (19), more stable (36), more frequently involved in domain fusion events (32), and are associated with high functional diversity (20). Our analysis shows two additional unique features of these domains: they lie in a tightly connected region of protein space and their motifs mix-and-join with a wider range of motifs.…”
Section: The Motif Network Reveals the Ubiquitous Reuse Of Motifs Inmentioning
confidence: 68%
“…[19][20][21]. By coloring the points according to domain characteristics, one can visually identify global properties of the protein universe (19,20). However, a map representation in low-dimensional Euclidean space implicitly suggests that similarity among domains is transitive (i.e., that similarity within the pairs AB and BC implies that AC is similar too); we know that this is often not the case (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We appreciate the anonymous reviewers' suggestions and efforts a conservative estimate, there are more than 10 10 proteins on earth [2] in addition to the engineered ones. The importance of the knowledge of proteins shape, the abundance of proteins of unknown structures, and the limitations of the experimental methods have all contributed to the need for the computational methods to predict the three dimensional shape of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The Automated Protein Subfamily Identification and Classification by (Brown et al, 2007) enables improved specificity of functional inference and facilitates prediction of functional shifts in new sequences. (Choi and Kim, 2006) address by evolution of protein structural classes and protein sequence families. They were report on the development of an efficient sub-graph mining technique and its application to finding characteristic sub-structural patterns within protein structural families.…”
Section: Introductionmentioning
confidence: 99%